Lived experiences of a community regarding its involvement in a university community-based education programme - Charlotte Engelbrecht; Ntombifikile G. Mtshal; Ntombizodwa S.B. Linda (AOSIS, 2013)
Background: Community involvement is one of the crucial principles in the implementation of successful community-based education programmes. However, a gap continues to exist between the rhetoric of this principle and the reality of involving or engaging communities in the education of health professionals. Objectives: This study investigated the experiences of a community regarding its involvement in a community-based education programme offered by a university nursing school in Durban, South Africa. Methods: An interpretive existentialist-phenomenological design was employed for its richness in extracting human experiences. Individual interviews were held with school teachers and coordinators from non-government organisations, whilst focus groups were used for school children and community health workers. Although focus group discussions are not well suited for phenomenological studies, they can promote active participation and reduce possible intimidation by providing support through group interaction. Analysis of data was guided by Schweitzer's model for analysing phenomenological data. Results: Themes that emerged from the data include: (1) Community experience of unmet expectations; (2) Benefits to the community from its involvement in the University Nursing School community-based education programme; (3) Existing partnership between the community and the university; (4) Sharing in the case-based learning activities; (5) Awareness of available services, human rights and self-reliance. Conclusion: The researched community indeed benefited in its participation in the University Nursing School (UNS) CBE programme. However, there is a need to improve the communication between partners to make the partnership more sustainable through close relationships and interaction. There is also a need for further research on related aspects of the community's involvement.